CASE REPORT: THE PROVISION OF INTERVENTION TENS AND NEURO MOBILIZATION IN PATIENTS WITH CERVICAL ROOT SYNDROME (CRS) - Irfan, Naufal; Perdana, Suryo Saputra (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this article is to show the benefits of physiotherapy modalities in the form of Trancutaneus Electrical Nerve Stimulation (TENS) and Neuro Mobilization in patients with Cervical Root Syndrome (CRS). It begins with the presence of auctivity will cause excessive effect on a person, such as a complaint on the muscular system (musculoskeletal) in the form of complaints of pain, pain, fatigue and other. This research using this type of research is a case study. The implementation of the research made in In RSUP Dr. Sardjito. After getting physiotherapy treatment for 3 times using TENS and Neuro Mobilization obtained positive results such as a decrease in pain silent, press, and motion, the presence of reelkatan LGS, and increased aktivity. In addition, it was found that the presence of a decrease in pain in cervical, i.e. there is the addition of ROM on some field of motion. Another thing is there is a drop points NDI which signifies that the patient is gradually able to release its dependence with other people in the activity diary.